2012
DOI: 10.1152/ajpcell.00010.2012
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 in porcine lens epithelium regulates hemichannel-mediated ATP release and Na-K-ATPase activity

Abstract: In several tissues, transient receptor potential vanilloid 4 (TRPV4) channels are involved in the response to hyposmotic challenge. Here we report TRPV4 protein in porcine lens epithelium and show that TRPV4 activation is an important step in the response of the lens to hyposmotic stress. Hyposmotic solution (200 mosM) elicited ATP release from intact lenses and TRPV4 antagonists HC 067047 and RN 1734 prevented the release. In isosmotic solution, the TRPV4 agonist GSK1016790A (GSK) elicited ATP release. When p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(106 citation statements)
references
References 40 publications
2
101
0
Order By: Relevance
“…Whether the association between pannexins and actin in Figure 5 indicates a more direct role in mechanosensitivity or is merely a reflection of the cultured condition, as found in cortical astrocytes (Oberheim et al 2009), remains to be determined. An upstream role for TRPV4 has been implicated in the swelling-activated ATP release from pannexins in lens (Shahidullah et al 2012) and airway epithelial cells (Seminario-Vidal et al 2011). However, experiments to determine a role of TRPV4 in the present study were inconclusive due to the substantial effect of inhibitor HC067047 on the luciferase standard curve (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Whether the association between pannexins and actin in Figure 5 indicates a more direct role in mechanosensitivity or is merely a reflection of the cultured condition, as found in cortical astrocytes (Oberheim et al 2009), remains to be determined. An upstream role for TRPV4 has been implicated in the swelling-activated ATP release from pannexins in lens (Shahidullah et al 2012) and airway epithelial cells (Seminario-Vidal et al 2011). However, experiments to determine a role of TRPV4 in the present study were inconclusive due to the substantial effect of inhibitor HC067047 on the luciferase standard curve (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…GSK1016790A induces a Ca 2ϩ increase in several different cell types at nanomolar levels (13,14,33). For example, in TRPV4-transfected HeLa cells, GSK1016790A produces a dose-dependent Ca 2ϩ increase with an EC 50 of 3.3 nM (14).…”
Section: Discussionmentioning
confidence: 99%
“…With a molecular weight of 668, PI would be excluded by most channels but not hemichannels. It is interesting that both increased PI uptake and ATP release in hyposmotic solution were blocked by RN 1734, a very different channel blocker that interferes with TRPV4 channels (Shahidullah et al, 2012b). Moreover, it was found that PI entry into the lens epithelium was increased by more than twofold in lenses exposed to a TRPV4 agonist GSK1016790A (GSK).…”
Section: Recent Findings Regarding Purines In the Eyementioning
confidence: 99%